Hemophilia Liver Transplantation Observational Study (HOTS) - Ragni, Margaret V. (Liver Transpl, 2017)
Hepatitis C (HCV) infection is the leading cause of liver disease in hemophilia. In those with HIV/HCV co-infection, the rate of liver disease progression is greater than in HCV mono-infected individuals. Despite antiretroviral therapy which slows HCV liver disease progression, some require transplantation. Whether transplant outcomes are worse in hemophilic (H) than non-hemophilic (NH) candidates is unknown. In order to determine rates and predictors of pre- and post-transplant survival, we conducted a retrospective observational study utilizing United Network for Organ Sharing (UNOS) national transplant registry data, comparing HCV+ H and NH candidates. We identified 2,502 HCV+ liver transplant candidates from eight U.S. university-based transplant centers, between January 1, 2004 to December 31, 2010, including 144 HIV+ (6%) and 2,358 HIV−; 36 H (1%) and 2,466 NH; 1,213 (48%) transplanted and 1,289 not transplanted. Other than male predominance and younger age, each p<0.001, baseline data were comparable between H and NH. In univariate analysis, 90-day pre-transplant mortality was associated with higher baseline MELD, HR=1.15, p<0.001, lower baseline platelet count, HR=1.11 per 25k/JL, p=0.04, and having HIV/HCV+ hemophilia, p=0.003. In multivariate analysis, pre-transplant mortality was associated with higher MELD (p<0.001) and was significantly greater in HIV+ than HIV− groups (p=0.001), but did not differ between HIV+ H and NH, HR=1.7, p=0.36. Among HIV/HCV+, post-transplant mortality was similar between H and NH, despite lower CD4 in H, p=0.04. CONCLUSIONS: This observational study confirms that hemophilia per se does not have a specific influence on transplant outcomes, and that HIV infection increases the risk of mortality in both H and NH patients.